High in vitro activity of DIS-73285, a novel antimicrobial with a new mechanism of action, against MDR and XDR Neisseria gonorrhoeae. (26th July 2020) - Jacobsson, Susanne; Mason, Clive; Khan, Nawaz; Meo, Paul; Unemo, Magnus
Abstract: Background: The rising incidence of antimicrobial resistance in Neisseria gonorrhoeae may result in untreatable gonorrhoea in certain circumstances and development of novel antimicrobials is urgently needed. Objectives: To evaluate the in vitro activity of a novel small-molecule antimicrobial with a new mechanism of action, DIS-73285, against a large geographically, temporally and genetically diverse collection of clinical N. gonorrhoeae isolates and reference strains, including various types of high-level resistant, MDR and XDR gonococcal isolates ( n  =   262). Methods: MICs (mg/L) of DIS-73285 were determined by agar dilution and by Etest for ceftriaxone, cefixime, azithromycin, ciprofloxacin, ampicillin, spectinomycin and tetracycline. Results: DIS-73285 was substantially more potent than any of the currently or previously used therapeutic antimicrobials, with MICs ranging from ≤0.001 to 0.004 mg/L, and the MIC50, MIC90 and modal MIC all ≤0.001 mg/L (lowest MIC tested). No correlation with the MICs of DIS-73285 and the MICs of any of the currently or previously used antimicrobials was observed. Conclusions: The novel chemotype, small-molecule antimicrobial DIS-73285, demonstrated high in vitro potency against all tested N. gonorrhoeae isolates. Further in vitro and in vivo studies, evaluating efficacy, resistance emergence, pharmacokinetic/pharmacodynamic parameters, toxicity and safety, should be conducted to evaluate DIS-73285 as a therapy specifically for urogenital and extra-genital gonorrhoea.